PENERAPAN PROBLEM BASED-LEARNING MELALUI LESSON STUDY PADA PEMBELAJARAN PPKN UNTUK MENINGKATKAN PARTISIPASI AKTIF DAN KERJASAMA SISWA DALAM DISKUSI KELOMPOK - Ken Restisiwi; Lutfi Istikharoh (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT This article presents the result of implementing Problem-based Learning through Lesson Study in Civics class as an effort of enhancing students' participation and collaboration during class discussions. The implementation of Problem-based Learning through Lesson Study was conducted in a private school under Muhammadiyah organization in Distric Purbalingga, Central Java, namely MTs Muhammadiyah 01 Purbalingga. In Civics Class at the school investigated, the learning process was commonly dominated by lecturing session which made the students passive and found monotonous atmosphere of learning which consequently resulted on meaningless learning. This condition affected to the students' activeness which belonged to low category. Therefore a better design of learning by implementing Problem-based Learning through Lesson Study was needed to cope with the problem. Lesson Study was done in 2 cycles and is still continuing until now. The action was intended to make the students more active and participative during the Civics lesson especially in class discussion sessions. The method which was used is qualitative method with 36 students in grade 8E of MTs Muhammadiyah 01 Purbalingga participated. During two times of plan-do-see actions in Lesson Study, 8 of 9 groups in Civics class or 80% of the whole students was good at participating in group and class discussions. The finding found in the two cycles of Lesson Study gives a proof that the implementation of Problem-based Learning contributes positively to the students' participation and collaboration in Civics class. Keywords: Plan, Do, See, Participation, Collaboration